Conceptual aspects of modern innovation policy - Omelyanenko, Vitaliy; Kudrina, Olga; Semenikhina, Olena; Zihunov, Vasily; Danilova, Olena; Liskovetska, Tetiana (European Journal of Sustainable Development, 2020)
The country’s participation in the processes of high technology development and transfer depends on: the level of its socio-economic development; the effectiveness of identifying innovative priorities; the developing an international strategy. This necessitates the development of theoretical foundations and practical recommendations for countries’ participation in high technology development processes in the global innovation system. We propose to consider high technology analysis as an analysis of public policy (interpretive analytics) and research in science and technology and technology assessment. Recently, an approach has come to the fore, in which it is necessary to focus not so much on absolute leaders who have already built their own chain of creation of innovations (from basic research to competitive companies), but more to develop their own unique competencies. The factor of formation of competitive innovative systems is creation of unique innovative environment on the basis of combination of technological basis, innovative economy and socio-cultural system. Keywords: innovation policy, high technology, innovative landscapes, clusters, human resources, technology transfer